Capital Budgeting Practices in India - Soni, Kashyap (2006)
This study reports the results of surveys of the capital budgeting techniques of BSE 500 companies in India. The results of the study indicate the prevalent use of the IRR and the payback method as primary and secondary criterion. This is consistent to the proposition that the theory-practice gap has narrowed in recent years. The survey questionnaires included topics such as use of capital budgeting decisions and risk analysis techniques. As for the non financial criteria, 54% of the companies considered strategic alignment as an important factor in making investment decisions. Comparatively new techniques like EVA have found a few users compared to other complex techniques like Real Options and Monte Carlo Simulations. A comparison with past studies conducted around the world is also made to analyze differences in practices.